Synthesis and anti-melanoma effect of 3-O-prenyl glycyrrhetinic acid against B16F10 cells via induction of endoplasmic reticulum stress-mediated autophagy through ERK/AKT signaling pathway - Nazir, Lone A.; Shahid, Naikoo H.; Amit, Kumar; Umar, Sheikh A.; Rajni, Sharma; Bharate, Sandip; Sangwan, Pyare L.; Tasduq, Sheikh Abdullah (Frontiers in Oncology, 2022)
Melanoma is an aggressive form of cancer with poor prognosis and survival rates and limited therapeutic options. Here, we report the anti-melanoma effect of 3-O-prenyl glycyrrhetinic acid (NPC-402), a derivative of glycyrrhtinic acid, from a reputed medicinal plant Glycyrrhiza glabra against B16F10 cells. We studied the cytotoxic effect of NPC-402 on melanoma cells and investigated the role of mitogen-activated protein (MAP) kinase, AKT axis, and endoplasmic reticulum (ER) stress/unfolded protein response (UPR)-mediated autophagy as the involved signaling cascade by studying specific marker proteins. In this study, 4-phenylbutyric acid (4PBA, a chemical chaperone) and small interference RNA (siRNA) knockdown of C/EBP Homologous Protein (CHOP)/growth arrest- and DNA damage-inducible gene 153(GAD153) blocked NPC-402-mediated autophagy induction, thus confirming the role of ER stress and autophagy in melanoma cell death. NPC-402 induced oxidative stress and apoptosis in melanoma cells, which were effectively mitigated by treatment with N-acetylcysteine (NAC). In vivo studies showed that intraperitoneal (i.p.) injection of NPC-402 at 10 mg/kg (5 days in 1 week) significantly retarded angiogenesis in the Matrigel plug assay and reduced the tumor size and tumor weight without causing any significant toxic manifestation in C57BL/6J mice. We conclude that NPC-402 has a high potential to be developed as a chemotherapeutic drug against melanoma.